(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2022)
The value of history to Zambian society is indisputable. A person who does not know their history will have no sense of belonging and hence will have very little motivation to contribute to the well-being of the communities in which they live. According to Simakando, “to an ordinary person who has no historical lenses that can help him or her to appreciate the value of history, it is very difficult to appreciate why history should be taught to learners in Zambia” (Simakando, 2020: 9). It is for this reason that I write on the historical challenges in relation to the Zambian curriculum and see the appreciation of history by both learners and people who value human development.